ADVANTAGES OF TELEMEDICINE IN NEUROREHABILITATION AND QUALITY OF LIFE IMPROVEMENT (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
This paper focuses on researching the potential of telerehabilitation for improving the quality of life of patients. As telemedicine is gaining more and more ground in various medical fields, its application in neurorehabilitation can reduce costs, improve the training process, facilitate the communication between patients and therapists, as well as ensure the supervision of the rehabilitation progress through technology means. After analyzing the existing studies related to telemedicine in neurorehabilitation, we draw the line to show the advantages and drawbacks of the process. We then present our current work, the INREX-VR project for neurorehabilitation, which has the goal of helping people recover easier from neurological disorders with the help of virtual reality, motion detection, biosensors and telerehabilitation.
Keywords: Telemedicine; Telerehabilitation; Neurorehabilitation; Virtual reality; Assistive technology